Analysis of Factors Influencing the Improvement of Psychological Well-Being of Ex-Drug Users Among Adolescents; A Systematic Review - Barokah, Khoiriah; Kiki Andi Karos, TS (Edukasi: Journal of Educational Research, 2023)
The problem of drug abuse is still a concern for the whole world, including Indonesia. Especially among adolescents as the nation's next generation certainly needs more attention in the process of growth and development. So we need a solution to save teenagers from addiction to drug abuse and get good psychological well-being. Purpose: to identify and analyze the factors that can influence the improvement of the psychological well-being of ex-drug addict youth based on previous research. Methods: literature review using PRISMA by: identifying articles from the database publish or perish, Scopus, ProQuest and Science Direct use keyword 141 articles were relevant, then selected by meeting the inclusion criteria, seven articles were obtained. Articles published from 2017-2022, from the journal psychology and adolescent nursing. Results: There are several factors that can improve the psychological well-being of adolescent former drug users, namely by undergoing rehabilitation properly, using Islamic counseling model techniques, developing personal character, therapeutic community and training mixed martial arts, hope, social support, Positive emotion and engagement.